Pendekatan Integratif Literasi Digital Siswa Madrasah Aliyah Negeri 1 Pontianak melalui Edukasi E-Commerce, E-Wallet, dan Paylater di Era Revolusi Industri 4.0 - Ananda Archie; Mahardika Agung Madepo; Arninda Arninda; Lina Budiarti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This community service program aims to enhance digital literacy among students of Madrasah Aliyah Negeri 1 Pontianak through education on e-commerce, e-wallets, and paylater services. In the era of the Industrial Revolution 4.0, the high internet usage among teenagers is not matched by sufficient understanding of digital transactions and financial risks. The program involved 77 students and was delivered using interactive methods and digital learning media. The materials covered the concepts, benefits, and risks of using digital platforms, especially paylater services. The results show a significant improvement in students’ understanding of online transactions, digital security, and responsible financial decision-making. This activity not only had an educational impact but also helped shape students into smart digital consumers. The program is recommended for integration into the formal school curriculum to better prepare the younger generation for the challenges of the digital economy in a sustainable way.